The first record of the genus Pseudoptilolepis SNYDER (Diptera: Muscidae) in Argentina - Patitucci, Luciano Damián (2009)
The genus Pseudoptilolepis SNYDER, 1949 and the species P. confusa SNYDER, 1949 are recorded for the first time in Argentina, extending the Neotropical distribution of both taxa. The specimens were collected in Corrientes province, flying around the fruiting body of a stinkhorn fungus (Phallaceae). A modification to the key to Argentine Muscidae is given.